Secondary battery and electronic device

By providing a hydrophobic composite coating on the surface of the positive electrode material layer of the lithium-ion battery, the problem of reacting high-nickel positive electrode material with air to generate residual lithium compounds is solved, and the effect of improving energy density and cycling performance is achieved.

CN120184414APending Publication Date: 2025-06-20NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510360486.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

The high-nickel cathode materials in lithium-ion batteries are easily reacted with moisture and carbon dioxide in the air to produce residual lithium compounds, resulting in a decrease in energy density and cycling performance.

Method used

A hydrophobic composite coating is provided on the surface of the positive electrode material layer, including hydrophobic polymer material and inert substance particles, to adjust the contact angle and impedance to reduce the production of residual lithium compounds.

Benefits of technology

By reducing the contact between the positive electrode material layer and moisture in the air, the generation of residual lithium compounds is reduced, and the energy density and circulation performance of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120184414A_ABST
    Figure CN120184414A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and an electronic device, the secondary battery comprises a positive pole piece, the positive pole piece comprises a positive pole material layer, a hydrophobic composite coating and a positive pole current collector, the positive pole material layer is located between the hydrophobic composite coating and the positive pole current collector, the contact angle theta of the hydrophobic composite coating is greater than or equal to 90 degrees and less than or equal to 150 degrees; the impedance of the positive pole piece is R < omega >, and R is not less than 0.05 and not more than 2. The secondary battery provided by the invention has relatively high energy density and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technologies, and particularly to a secondary battery and an electronic device. Background Art

[0002] Secondary batteries, such as lithium-ion batteries, are widely used in application scenarios such as portable electronic devices and electric vehicles due to their fast charging speed, high working voltage, and low self-discharge rate. In order to meet the increasing demand for energy density in the above application scenarios, high-energy-density positive electrode active materials have been gradually developed.

[0003] For example, high-nickel positive electrode materials are applied to lithium-ion batteries due to their relatively high theoretical specific capacity. However, positive electrode materials with a relatively high nickel content are prone to form independent lithium-oxygen coordination bond compounds by themselves, and are likely to react with moisture and carbon dioxide in the air to generate residual lithium compounds such as Li2CO3 and LiOH, thereby reducing the specific capacity per gram of the high-nickel positive electrode material, affecting the performance of its specific capacity per gram in lithium-ion batteries, and further affecting the energy density of lithium-ion batteries. At the same time, the generation of residual lithium compounds will also affect the cycle performance of lithium-ion batteries. Therefore, it is difficult to balance the energy density and cycle performance of lithium-ion batteries. Summary of the Invention

[0004] The purpose of the present application is to provide a secondary battery and an electronic device, by reducing the generation of residual lithium compounds on the surface of the positive electrode material layer, to improve the energy density of the secondary battery and balance the cycle performance.

[0005] It should be noted that in the summary of the invention of the present application, lithium-ion batteries are used as examples of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0006] The first aspect of the present application provides a secondary battery, which includes a positive electrode tab. The positive electrode tab includes a positive electrode material layer, a hydrophobic composite coating, and a positive electrode current collector. The positive electrode material layer is located between the hydrophobic composite coating and the positive electrode current collector. The hydrophobic composite coating includes a hydrophobic polymer material and inert substance particles. The contact angle of the hydrophobic composite coating is θ, and 90° ≤ θ ≤ 150°. In some embodiments of the present application, 100° ≤ θ ≤ 130°. The impedance of the positive electrode tab is R Ω, and 0.05 ≤ R ≤ 2. In some embodiments of the present application, 0.1 ≤ R ≤ 1. When the contact angle θ of the hydrophobic composite coating is within the above range and the impedance of the positive electrode tab is R within the above range, it can not only reduce the contact between the positive electrode material layer and moisture in the air, reduce the generation of residual lithium compounds, but also the positive electrode tab has a relatively small impedance, which is beneficial to balancing the energy density, cycle performance, and kinetic performance of the secondary battery.

[0007] In some embodiments of the present application, based on the area S of the positive electrode material layer, the area of the hydrophobic composite coating is S1, and 20% ≤ S1 / S × 100% ≤ 60%. In some embodiments of the present application, 30% ≤ S1 / S × 100% ≤ 50%. By adjusting S1 / S × 100% within the above range, the positive electrode sheet has a good hydrophobic effect, and at the same time, reserving a suitable area without the hydrophobic composite coating is beneficial to the storage of the electrolyte and the transmission of active ions, thereby facilitating the improvement of the energy density, cycle performance, and kinetic performance of the lithium-ion battery.

[0008] In some embodiments of the present application, the adhesion force between the positive electrode sheet and the separator is F N / m, and 10 ≤ F ≤ 40. The adhesion force F between the positive electrode sheet and the separator within the above range indicates that there is good adhesion between the positive electrode sheet and the separator, which is thus beneficial to further improving the cycle performance of the secondary battery.

[0009] In some embodiments of the present application, the thickness of the hydrophobic composite coating is d μm, and 0.2 ≤ d ≤ 1.2. In some embodiments of the present application, 0.3 ≤ d ≤ 0.7. By adjusting d within the above range, it is beneficial to improve the energy density and cycle performance of the secondary battery. At the same time, the value of d within the above range is also beneficial to controlling the overall thickness of the secondary battery within a suitable range, taking into account the energy density of the secondary battery.

[0010] In some embodiments of the present application, based on the mass of the hydrophobic composite coating, the mass percentage content m1 of the inert substance particles is 10% to 30%, and the mass percentage content m2 of the hydrophobic polymer material is 70% to 90%; the inert substance particles include at least one of boehmite, diaspore, or quartz sand; the hydrophobic polymer material includes at least one of polyvinylidene fluoride, polysiloxane, polyurethane, or polymethacrylate. The m within the above range is beneficial to taking into account the kinetic performance and cycle performance of the secondary battery. In addition, selecting the inert substance particles within the above range and / or the hydrophobic polymer material within the above range is beneficial to improving the kinetic performance of the secondary battery and further enhancing the cycle performance of the secondary battery.

[0011] In some embodiments of the present application, the average particle size of the inert substance particles is D1 nm, and 100 ≤ D1 ≤ 500. By adjusting D1 within the above range, the particle size of the inert substance particles is moderate, which is beneficial to improving the cycle performance and processing performance of the secondary battery.

[0012] In some embodiments of the present application, the weight-average molecular weight of the hydrophobic polymer material is W g / mol, where 100,000 ≤ W ≤ 500,000. By controlling W within the above range, it is beneficial to the coating of the hydrophobic composite coating slurry on the surface of the positive electrode material layer, and thus beneficial to improving the processing performance of the positive electrode sheet. At the same time, the obtained hydrophobic polymer composite layer is not easily cracked during the cycling process of the secondary battery. Therefore, the value of W within the above range is beneficial to improving the cycling performance of the secondary battery.

[0013] In some embodiments of the present application, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes nickel element. In some embodiments of the present application, the positive electrode active material includes lithium nickel cobalt manganese oxide. Based on the total molar amount of metal elements other than lithium, the molar percentage content of nickel element is M, where 50% ≤ M ≤ 95%. By selecting a positive electrode active material including nickel element and M within the above range, the obtained positive electrode active material has a high specific capacity, and when combined with the hydrophobic composite coating of the present application, it is also beneficial to further improve the energy density and cycling performance of the secondary battery.

[0014] In some embodiments of the present application, the average particle size of the positive electrode active material is D2 μm, where 5 ≤ D2 ≤ 15. By controlling D2 within the above range, the positive electrode active material has a moderate specific surface area, which is beneficial to the uniform coating of the hydrophobic composite coating on the surface of the positive electrode material layer, and reduces the risk of cracking and peeling of the hydrophobic composite coating during the cycling process of the secondary battery, thus being beneficial to further improving the cycling performance of the secondary battery.

[0015] The second aspect of the present application provides an electronic device, which includes the secondary battery in any of the foregoing embodiments.

[0016] Advantages of the present application:

[0017] The present application provides a secondary battery and an electronic device. By providing a hydrophobic composite coating on the surface of the positive electrode material layer, the contact angle θ between the positive electrode sheet and water ranges from 90° to 150°, and the impedance R satisfies the range of 0.05 Ω to 2 Ω. By providing the above hydrophobic composite coating and θ, R within the above range, it is not only beneficial to reduce the contact between the positive electrode material layer and moisture and carbon dioxide in the air, thereby reducing the generation of residual lithium compounds on its surface and promoting the exertion of the specific capacity of the positive electrode active material, but also beneficial to improving the kinetic performance of the secondary battery, thus being beneficial to improving the energy density of the secondary battery and taking into account the cycling performance.

[0018] Of course, it is not necessary for any product or method implementing the present application to achieve all the above advantages simultaneously. Brief Description of the Drawings

[0019] To more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the accompanying drawings required for the description of the embodiments. Obviously, the accompanying drawings in the following description are only some embodiments of the present application. For those of ordinary skill in the art, other embodiments can also be obtained based on these drawings.

[0020] Figure 1 Schematic diagram of the structure of a lithium-ion battery according to an implementation scheme of the present application;

[0021] Figure 2 Scanning electron microscope photograph of one surface of the positive electrode sheet in Example 1-1;

[0022] Figure 3 For Figure 2 Partial enlarged view;

[0023] Figure 4 Scanning electron microscope photograph of the positive electrode sheet in Example 1-1 along its own thickness direction. Detailed implementation manners

[0024] The following will clearly and completely describe the technical solutions in the present application in combination with the embodiments and the accompanying drawings of the present application. Obviously, the described embodiments are only some embodiments of the present application, rather than all embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0025] It should be noted that in the specific implementation manners of the present application, a lithium-ion battery is taken as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0026] The positive electrode material of a secondary battery is likely to react when contacting with moisture and carbon dioxide in the air, generating residual lithium compounds, which will not only affect the capacity per gram of the positive electrode material and reduce the energy density of the secondary battery, but also affect the cycle performance of the secondary battery. In particular, positive electrode materials with relatively high capacities such as high-nickel positive electrode materials and lithium-rich manganese-based positive electrode materials are more significantly affected. Therefore, by setting a hydrophobic coating on the surface of the positive electrode material layer, the contact between the positive electrode material layer and moisture in the air can be reduced, thereby reducing the generation of residual lithium compounds. However, generally, the hydrophobic performance of the hydrophobic coating is poor, and it cannot isolate the positive electrode material layer from the air well. At the same time, the introduction of the hydrophobic coating usually significantly reduces the conductivity of the positive electrode sheet and increases the internal resistance of the positive electrode sheet, thereby affecting the rate performance and cycle life of the secondary battery. Based on the above problems, the present application provides a secondary battery and an electronic device, which can reduce the generation of residual lithium compounds on the surface of the positive electrode material layer and relieve the increase in the impedance of the positive electrode sheet, thereby improving the energy density and cycle performance of the secondary battery.

[0027] A first aspect of the present application provides a secondary battery, which includes a positive electrode plate. The positive electrode plate includes a positive electrode material layer, a hydrophobic composite coating, and a positive electrode current collector. The positive electrode material layer is located between the hydrophobic composite coating and the positive electrode current collector. The contact angle of the hydrophobic composite coating is θ, and 90° ≤ θ ≤ 150°. In some embodiments of the present application, 100° ≤ θ ≤ 130°. For example, θ can be 90°, 95°, 100°, 105°, 110°, 115°, 120°, 125°, 130°, 135°, 140°, 145°, 150°, or a range composed of any two of these values. When θ < 90°, the hydrophobic performance of the hydrophobic composite coating is poor, and it cannot effectively isolate the positive electrode material layer from moisture in the air. The positive electrode material layer is still prone to generating residual lithium compounds, which affects the energy and cycle performance of the secondary battery. Therefore, when the contact angle θ of the hydrophobic composite coating is within the above range, it is beneficial to reduce the contact between the positive electrode material layer and moisture in the air, thereby reducing the generation of residual lithium compounds and improving the energy density and cycle performance of the secondary battery.

[0028] In the present application, the impedance of the positive electrode plate is R Ω, and 0.05 ≤ R ≤ 2. In some embodiments of the present application, 0.1 ≤ R ≤ 1. For example, R can be 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, or a range composed of any two of these values. Generally, after a hydrophobic coating is provided on the positive electrode material layer, it will affect the transmission of active ions, such as lithium ions, in the secondary battery, increasing the impedance of the positive electrode plate, such as R > 2, and further affecting the kinetic performance and cycle performance of the lithium-ion battery. The hydrophobic composite coating of the present application can improve the hydrophobic performance of the positive electrode plate while maintaining good ion-conducting performance, reducing the internal resistance of the positive electrode plate, and thus taking into account the energy density, kinetic performance, and cycle performance of the secondary battery. It should be noted that the above R refers to the impedance of the positive electrode plate in the area where the hydrophobic composite coating is provided.

[0029] Therefore, for the secondary battery provided by the present application, a hydrophobic composite coating is provided on the surface of the positive electrode material layer, which can not only reduce the contact between the positive electrode material layer and moisture in the air and reduce the generation of residual lithium compounds, but also the positive electrode plate has a small impedance, which is beneficial to taking into account the energy density, cycle performance, and kinetic performance of the secondary battery.

[0030] The present application does not particularly limit the preparation method of the above positive electrode plate, as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode plate includes but is not limited to the following steps:

[0031] First, prepare the slurry for the positive electrode material layer. Mix inert material particles, a hydrophobic polymer material, and a solvent to obtain a hydrophobic composite coating slurry. Then, set the slurry for the positive electrode material layer on at least one surface of the positive electrode current collector and dry it. Next, use a doctor blade coating, spraying, or chemical vapor deposition method to set a hydrophobic composite coating on one surface of the positive electrode material layer, and obtain the positive electrode plate after drying and cold pressing. It should be noted that during the coating process of the hydrophobic composite coating, the area S1 of the hydrophobic composite coating will be jointly affected by factors such as the solid content of the hydrophobic composite coating slurry, the thickness of the hydrophobic composite coating, the type of hydrophobic polymer material, and the coating process. When the solid content of the insulating layer slurry is higher, the thickness of the hydrophobic composite coating is thinner, or the viscosity of the hydrophobic polymer coating is lower, the area S1 of the obtained hydrophobic composite polymer coating is usually smaller. At the same time, the method of setting the hydrophobic composite coating will also affect the size of S1. There is no particular limitation on the type of solvent in this application, as long as the purpose of this application can be achieved. For example, the solvent can include, but is not limited to, at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and dimethyl sulfoxide (DMSO). There is no particular limitation on the range of the solid content in this application, as long as the purpose of this application can be achieved. For example, the range of the solid content can be 3 wt% to 30 wt%. There is no particular limitation on the drying temperature and time of the hydrophobic composite coating in this application, as long as the purpose of this application can be achieved. For example, the drying temperature can be 100°C to 150°C, and the drying time can be 0.2 h to 2 h. It should be noted that cold pressing has basically no effect on the thickness and area of the hydrophobic composite coating.

[0032] Taking the change in the solid content as an example, when the solid content of the hydrophobic composite coating slurry decreases, the solvent content in the hydrophobic composite coating slurry increases. During drying, the solvent volatilizes and causes more pores to form in the hydrophobic composite coating, and the area S1 of the obtained hydrophobic composite coating covering the positive electrode material layer decreases. Vice versa.

[0033] In some embodiments of this application, based on the area S of the positive electrode material layer, the area of the hydrophobic composite coating is S1, and 20% ≤ S1 / S × 100% ≤ 60%. In some embodiments of this application, 30% ≤ S1 / S × 100% ≤ 50%. For example, S1 / S × 100% can be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60% or a range composed of any two of these ratios. By regulating S1 / S × 100% within the above range, the positive electrode plate has a good hydrophobic effect, and at the same time, leaving a suitable area without the hydrophobic composite coating is beneficial to the storage of the electrolyte and the transmission of active ions, thereby being beneficial to reducing the generation of residual lithium compounds while taking into account the impedance, and thus being beneficial to improving the energy density, cycle performance, and kinetic performance of the lithium-ion battery.

[0034] In some embodiments of the present application, the adhesion force between the positive electrode plate and the separator is F N / m, where 10 ≤ F ≤ 40. For example, F can be 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40, or a range composed of any two of these values. When the adhesion force F between the positive electrode plate and the separator is within the above range, it indicates that there is good adhesion between the positive electrode plate and the separator, which is beneficial to further improving the cycling performance of the secondary battery.

[0035] In some embodiments of the present application, the thickness of the hydrophobic composite coating is d μm, where 0.2 ≤ d ≤ 1.2. In some embodiments of the present application, 0.3 ≤ d ≤ 0.7. For example, d can be 0.2, 0.3, 0.33, 0.36, 0.4, 0.43, 0.48, 0.5, 0.52, 0.57, 0.6, 0.63, 0.68, 0.7, 0.8, 0.9, 1, 1.1, 1.2, or a range composed of any two of these values. By adjusting d within the above range, it is beneficial for the hydrophobic coating to better play its hydrophobic role, reduce the contact between the positive electrode material layer and moisture in the air, reduce the generation of residual lithium compounds, and thus improve the energy density and cycling performance of the secondary battery. At the same time, the value of d within the above range is also beneficial for controlling the overall thickness of the secondary battery within a suitable range, taking into account the energy density of the secondary battery.

[0036] In some embodiments of the present application, based on the mass of the hydrophobic composite coating, the mass percentage content m1 of the inert substance particles is 10% to 30%, and the mass percentage content m2 of the hydrophobic polymer material is 70% to 90%. For example, m1 can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, or a range composed of any two of these ratios. For example, m2 can be 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, or a range composed of any two of these ratios. By adjusting m1 and m2 within the above range, the hydrophobic coating can not only have good porosity for the transport of active ions but also have good viscosity, enabling the hydrophobic coating to better adhere to the surface of the positive electrode material layer. Thus, m within the above range is beneficial for taking into account the kinetic performance and cycling performance of the secondary battery.

[0037] In some embodiments of the present application, the inert material particles include at least one of boehmite, diaspore or quartz sand. In some embodiments of the present application, the hydrophobic polymer material includes at least one of polyvinylidene fluoride, polysiloxane, polyurethane or polymethacrylate. Among them, the polysiloxane includes at least one of polydimethylsiloxane or polymethylphenylsiloxane. By selecting the inert material particles within the above range and / or the hydrophobic polymer material within the above range, the obtained hydrophobic composite coating has good adhesion, and the hydrophobic composite coating is not easy to fall off during the cycle performance of the secondary battery; at the same time, the hydrophobic composite coating also has a suitable porosity, which is beneficial to the transport of active ions. Therefore, selecting the inert material particles within the above range and / or the hydrophobic polymer material within the above range is beneficial to improving the kinetic performance of the secondary battery and further enhancing the cycle performance of the secondary battery.

[0038] In some embodiments of the present application, the average particle size of the inert material particles is D1 nm, where 100 ≤ D1 ≤ 500. For example, D1 can be 100, 120, 150, 180, 200, 220, 250, 280, 300, 320, 350, 380, 400, 420, 450, 480, 500 or a range composed of any two of these values. By controlling D1 within the above range, the particle size of the inert material particles is moderate, which is beneficial to the dispersion of the inert material particles in the hydrophobic polymer material. The distribution uniformity of the inert material particles in the obtained hydrophobic composite coating is good, and the thickness of the obtained positive electrode sheet is uniform. Therefore, it is beneficial to improve the cycle performance and processing performance of the secondary battery.

[0039] In some embodiments of the present application, the weight average molecular weight of the hydrophobic polymer material is W g / mol, where 100000 ≤ W ≤ 500000. For example, W can be 100000, 120000, 150000, 180000, 200000, 250000, 300000, 350000, 400000, 420000, 450000, 480000, 500000 or a range composed of any two of these values. By controlling W within the above range, it is beneficial to the coating of the hydrophobic composite coating slurry on the surface of the positive electrode material layer, and further beneficial to improving the processing performance of the positive electrode sheet. At the same time, the obtained hydrophobic polymer composite layer has good mechanical strength and is not easy to crack during the cycle of the secondary battery. Therefore, the value of W within the above range is beneficial to improving the cycle performance of the secondary battery.

[0040] In some embodiments of the present application, the positive electrode material layer includes a positive electrode active material, the positive electrode active material includes nickel element, and based on the total number of moles of metallic elements other than lithium element, the molar percentage content of nickel element is M, and 50% ≤ M ≤ 95%. For example, M can be 50%, 52%, 55%, 58%, 60%, 65%, 70%, 75%, 80%, 82%, 85%, 88%, 90%, 92%, 95% or a range composed of any two of these values. By selecting a positive electrode active material including nickel element and M within the above range, the obtained positive electrode active material has a high specific capacity, and when combined with the hydrophobic composite coating of the present application, it is also beneficial to further improve the energy density and cycling performance of the secondary battery.

[0041] In some embodiments of the present application, the positive electrode active material includes LiNi 0.95 Mn 0.05 O2.

[0042] In some embodiments of the present application, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the chemical formula is LiNi x Co y Mn z M m O2, where x + y + z + m = 1, 0.5 ≤ x ≤ 0.95, 0 < y ≤ 0.3, 0.05 ≤ z ≤ 0.3, 0 ≤ m ≤ 0.2. M is a doping element, and M is selected from at least one of Ag, Sn, Zn, Al, Mg, Mo, Cu, B, Ti, W, Zr, Ir, V, and Fe. Exemplarily, lithium nickel cobalt manganese oxide may include but is not limited to LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM111), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) or LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) or at least one of them.

[0043] In some embodiments of the present application, based on the mass of the positive electrode material layer, the mass percentage content of lithium nickel cobalt manganese oxide is greater than or equal to 80%. In some embodiments of the present application, the mass percentage content of lithium nickel cobalt manganese oxide is greater than or equal to 80% and less than or equal to 99.8%.

[0044] In some embodiments of the present application, the positive electrode material may further include other positive electrode active materials. For example, it may include but is not limited to at least one of lithium cobalt oxide (LiCoO₂), lithium manganese oxide (LiMn₂O₄), or lithium iron phosphate (LiFePO₄). The present application does not particularly limit the content of the above other positive electrode materials in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, based on the mass of the positive electrode active material layer, the mass percentage of the above other positive electrode active materials is 0% to 18%. In some embodiments of the present application, the average particle size of the positive electrode active material is D2 μm, where 5 ≤ D2 ≤ 15. For example, D2 can be 5, 5.5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 14.5, 15, or a range composed of any two of these values. By adjusting D2 within the above range, the positive electrode active material has a moderate specific surface area, which is conducive to the uniform coating of the hydrophobic composite coating on the surface of the positive electrode material layer and reduces the risk of cracking and peeling of the hydrophobic composite coating during the cycling process of the secondary battery, thereby being conducive to further improving the cycling performance of the secondary battery.

[0045] The positive electrode material layer may further include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (SuperP), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials, or conductive polymers. The conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nanofibers. The above metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum, or silver. The above conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene, or polypyrrole.

[0046] The present application does not particularly limit the binder, as long as the purpose of the present application can be achieved. For example, the binder may include but is not limited to at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamideimide, styrene-butadiene rubber, or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, based on the mass of the positive electrode material layer, the mass percentages of the conductive agent and the binder are each independently 0.1% to 5%.

[0047] The present application has no particular limitation on the positive current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil, or a composite current collector (such as an aluminum-carbon composite current collector), etc.

[0048] The present application has no particular limitation on the thickness of the positive current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive current collector is 5 μm to 20 μm, and the thickness of the positive electrode material layer is 30 μm to 120 μm.

[0049] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive current collector and the positive electrode material layer. The composition of the conductive layer has no particular limitation and may be a commonly used conductive layer in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular limitation on the conductive agent and the binder in the conductive layer. For example, it may be at least one of the above-mentioned conductive agents and the above-mentioned binders.

[0050] In the present application, the secondary battery further includes a negative electrode sheet, which includes a negative current collector and a negative electrode material layer provided on at least one surface of the negative current collector. The above-mentioned "the negative electrode material layer is provided on at least one surface of the negative current collector" means that the negative electrode material layer may be provided on one surface of the negative current collector along its thickness direction, or may be provided on two surfaces of the negative current collector along its thickness direction. It should be noted that the "surface" here may be the entire area of the surface of the negative current collector, or may be a partial area of the surface of the negative current collector. The present application has no particular limitation, as long as the purpose of the present application can be achieved.

[0051] The present application has no particular limitation on the negative current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or a composite current collector. Exemplarily, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.

[0052] The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include, but is not limited to, natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, lithiated TiO2-Li4Ti5O with a spinel structure 12 or at least one of Li-Al alloy.

[0053] In some embodiments of the present application, the negative electrode material layer may further include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the objectives of the present application can be achieved. For example, it may be at least one of the above-mentioned conductive agent and the above-mentioned binder. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent, and the binder in the negative electrode material layer, and those skilled in the art can select according to actual needs as long as the objectives of the present application can be achieved.

[0054] The present application does not particularly limit the thickness of the negative electrode material layer, as long as the objectives of the present application can be achieved. For example, the thickness of the negative electrode material layer is 30 μm to 120 μm.

[0055] The present application does not particularly limit the thickness of the negative electrode current collector, as long as the objectives of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm.

[0056] Optionally, the negative electrode sheet may further include a conductive layer, and the conductive layer is located between the negative electrode current collector and the negative electrode material layer. The present application does not particularly limit the composition of the conductive layer, and it may be a commonly used conductive layer in the art. For example, the conductive layer includes a conductive agent and a binder. The present application does not particularly limit the conductive agent and the binder in the conductive layer. For example, it may be at least one of the above-mentioned conductive agent and the above-mentioned binder.

[0057] In the present application, the secondary battery further includes a separator. The present application does not particularly limit the separator, as long as the objectives of the present application can be achieved. For example, the material of the separator may include, but is not limited to, at least one of polyolefins (PO) such as polyethylene (PE) and polypropylene (PP), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of the separator may include at least one of a woven film, a non-woven film, a microporous film, a composite film, a rolled film or a spun film.

[0058] In some embodiments of the present application, the separator may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.

[0059] Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer, an inorganic layer, or a layer formed by mixing a polymer and an inorganic substance.

[0060] In some embodiments of the present application, the inorganic layer comprises inorganic particles and a binder. There are no particular limitations on the inorganic particles in the present application. For example, the inorganic particles may include at least one of alumina, silica, magnesia, titania, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconia, yttria, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. There are no particular limitations on the binder in the present application. For example, the binder may be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer comprises a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, or polyvinylidene fluoride or poly(vinylidene fluoride - hexafluoropropylene).

[0061] In the present application, there are no particular limitations on the thickness of the separator, as long as the object of the present application can be achieved. For example, the thickness of the separator can be 3 μm to 30 μm.

[0062] In the present application, the secondary battery further comprises an electrolyte, and the electrolyte comprises a lithium salt and a non-aqueous solvent.

[0063] There are no particular limitations on the lithium salt in the present application, as long as the object of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalato)borate (LiBOB), or lithium difluoroborate. There are no particular limitations on the content of the lithium salt in the electrolyte in the present application, as long as the object of the present application can be achieved.

[0064] There are no particular limitations on the non-aqueous solvent in the present application, as long as the object of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds, or other organic solvents.

[0065] The above-mentioned carbonate compounds may include, but are not limited to, at least one of chain carbonate compounds, cyclic carbonate compounds, or fluorinated carbonate compounds. The above-mentioned chain carbonate compounds may include, but are not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), or methyl ethyl carbonate (MEC). The above-mentioned cyclic carbonates may include, but are not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), or vinylene ethylene carbonate (VEC). The fluorinated carbonate compounds may include, but are not limited to, at least one of fluorinated ethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethyl ethylene carbonate. The above-mentioned carboxylate compounds may include, but are not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, or caprolactone. The above-mentioned ether compounds may include, but are not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran. The above-mentioned other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate. The present application does not particularly limit the content of the non-aqueous solvent in the electrolyte as long as the object of the present application can be achieved.

[0066] The secondary battery further includes a housing for accommodating the positive electrode sheet, the separator, the negative electrode sheet, and the electrolyte, as well as other components known in the field of secondary batteries. The present application does not limit the above-mentioned other components. The present application does not particularly limit the housing, and it may be a housing well-known in the art as long as the object of the present application can be achieved. For example, the housing may be a hard shell housing or a flexible housing. The material of the hard shell housing may be metal. The present application does not limit the type of metal, and a metal hard shell housing known in the art may be used as long as the object of the present application can be achieved. The flexible housing may be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0067] The preparation process of the secondary battery of the present application is well-known to those skilled in the art, and the present application has no special limitations. For example, the preparation process of the secondary battery may include, but is not limited to, the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, and winding, folding, etc. as needed to obtain a wound structure electrode assembly, placing the electrode assembly into a housing, injecting electrolyte into the housing and sealing it to obtain a secondary battery. Alternatively, stack the positive electrode sheet, the separator, and the negative electrode sheet in sequence, and then fix the four corners of the entire laminated structure with tape to obtain a laminated structure electrode assembly, place the electrode assembly into a housing, inject electrolyte into the housing and seal it to obtain a secondary battery. In addition, an overcurrent protection element, a guide plate, etc. can also be placed in the housing as needed to prevent the pressure inside the secondary battery from rising and overcharging / discharging.

[0068] The second aspect of the present application provides an electronic device, which includes the secondary battery in any of the foregoing embodiments. Thus, the electronic device provided by the present application has good use performance.

[0069] The present application does not particularly limit the type of the electronic device, and it can be any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a headset, a video recorder, a liquid crystal TV, a portable cleaner, a portable CD player, a minidisc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a moped, a bicycle, a lighting fixture, a toy, a game console, a clock, a power tool, a flash, a camera, a large household battery, and a lithium-ion capacitor, etc.

[0070] Examples

[0071] Hereinafter, examples and comparative examples are given to more specifically illustrate the embodiments of the present application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0072] Testing methods and equipment:

[0073] Sampling of the positive electrode sheet:

[0074] At 25 °C, the lithium-ion battery is discharged at a constant current of 0.5C until the discharge cut-off voltage. The lithium-ion battery is disassembled under an argon atmosphere, and the positive electrode sheet is soaked in dimethyl carbonate solvent for 2 h and dried at 60 °C for 1 h to obtain the positive electrode sheet. Among them, the discharge cut-off voltage of the lithium-ion battery in the examples and comparative examples of this application is 3.0 V. It can be understood that when the voltage range marked on the outer package of the factory battery is 3.0 V to 4.45 V, the charge cut-off voltage is 4.45 V and the discharge cut-off voltage is 3.0 V. Unless otherwise specified, the charge cut-off voltage of the lithium-ion battery as an example in this application is 4.45 V and the discharge cut-off voltage is 3.0 V.

[0075] Unless otherwise specified, the above-obtained positive electrode sheet samples are used for testing in the following testing methods.

[0076] Contact angle θ:

[0077] A drop of deionized water is dropped on the surface of the positive electrode sheet sample, and the contact angle between the water drop and the surface of the positive electrode sheet is measured by an optical contact angle measuring instrument (SDC-200s). It should be noted that when the positive electrode sheet includes a hydrophobic coating, the above contact angle refers to the contact angle between the positive electrode sheet in the area where the hydrophobic coating is provided and water; when the positive electrode sheet does not include a hydrophobic coating, the above contact angle refers to the contact angle between the positive electrode sheet in the area where the positive electrode material layer is provided and water.

[0078] Impedance R of the positive electrode sheet:

[0079] The positive electrode sheet is cut into a circle with a diameter of 12 mm to obtain a positive electrode sheet sample. The positive electrode sheet, separator and negative electrode sheet are stacked in sequence and electrolyte is dropped to assemble a button cell.

[0080] The above separator and electrolyte are the same as those in Example 1-1, and the thickness of the lithium sheet is 0.4 mm.

[0081] Measurement of impedance:

[0082] The internal resistance of the lithium-ion battery is tested using the electrochemical impedance spectroscopy (EIS) technique. The impedance test is carried out on an electrochemical impedance spectrometer. The test frequency is from 100 kHz to 10 MHz, and the amplitude is from 5 mV to 10 mV. The impedance data at different frequencies during the test are recorded, including the real part (Z') and the imaginary part (Z"). An analysis software is used to plot the Nyquist diagram of Z' vs. Z". By fitting the equivalent resistance, the diameter of the semi-circle in the fitting curve is the impedance of the lithium-ion battery.

[0083] S1 / S×100%:

[0084] Take a positive electrode sheet sample, and use a scanning electron microscope (SEM) to select the area with an "island-like" morphology distribution in the positive electrode sheet as the area A where the hydrophobic composite coating is set. The area of area A is S1. Measure the total area S of the positive electrode material layer on the positive electrode sheet with a micrometer. Combine the SEM image processing software to perform threshold segmentation processing on the SEM image according to different contrasts, and calculate S1 / S×100%.

[0085] The adhesion force F between the positive electrode sheet and the separator:

[0086] Disassemble the lithium-ion battery, take out the bonded positive electrode sheet, separator, and negative electrode sheet together, and separate the negative electrode sheet to obtain an adhesion force test sample. Cut the above sample into a spline with a size of 100mm×20mm. Clamp one end of the positive electrode sheet on the tensile machine fixture, stretch it at 180°, turn on the tensile machine for testing, and pull the positive electrode sheet at a constant speed of 50mm / min until the positive electrode sheet is peeled off from the separator. After the test is completed, obtain the adhesion force F between the positive electrode sheet and the separator.

[0087] The thickness d of the hydrophobic composite coating:

[0088] Polish the cross-section of the positive electrode sheet sample along the thickness direction by ion polishing to obtain the cross-section of the electrode sheet. Observe and measure it at a magnification of 500 in the VHX5000 microscope. Set the dimensions of the area with the hydrophobic composite coating and the area without the hydrophobic composite coating along the above direction. Measure 10 points for the dimensions of the above two areas and take the average value as the thickness of each area, and calculate the difference between the thicknesses of the above two areas as d.

[0089] The average particle size D1 of the inert material particles:

[0090] Take a positive electrode sheet sample, dissolve the sample fully in tetrahydrofuran solvent, and filter it through a 0.6μm fine filter screen 3 times. Remove the powder sample filtered by the filter screen, which is the inert material particles. Dry the powder sample to prepare a transmission electron microscope sample (TEM). Select 10 particles without nickel element through TEM, measure their circumscribed circle diameters respectively, and calculate the average value as D1.

[0091] The average particle size D2 of the positive active material:

[0092] Take a positive electrode sheet sample, use a scanning electron microscope, combined with the energy dispersive spectrometer (EDS) of the SEM, in the area except the "island-like" morphology part, select 10 particles containing nickel element, measure their circumscribed circle diameters respectively, and calculate the average value as D2.

[0093] The weight-average molecular weight W of the hydrophobic polymer material:

[0094] Take a positive electrode sample, dissolve the sample thoroughly in a tetrahydrofuran solvent, and filter it through a 0.1 μm fine filter screen three times to remove inert material particles, positive electrode active materials, etc. in the sample, obtaining a uniform solution.

[0095] Then use gel permeation chromatography (GPC) to test the weight-average molecular weight of the sample: Inject the above solution into the GPC instrument. Separate through a porous gel column, and components with different molecular weights are eluted in sequence. Use a differential refractive index detector (such as to detect the eluted components. According to the calibration curve of the elution time and the standard sample (polyethylene), calculate the molecular weight distribution and weight-average molecular weight of the sample.

[0096] Molar percentage content M of nickel element:

[0097] Sample preparation: At an ambient temperature of 25 °C, disassemble the lithium-ion battery, take out the positive electrode, scrape the positive electrode material layer powder from the positive electrode, calcine it in an air atmosphere at 400 °C for 2 h, dissolve the sample thoroughly in a tetrahydrofuran solvent, and filter it through a 0.6 μm fine filter screen three times. Take the powder sample remaining on the filter screen to obtain a positive electrode material layer sample containing the positive electrode active material. Then take 0.4 g of the sample and dissolve it in 10 mL of aqua regia (concentrated hydrochloric acid (HCl) and concentrated nitric acid (HNO3) in a volume ratio of 3:1), dissolve it at 180 °C for 30 min and then cool it to room temperature, and make the volume of the sample up to 100 mL.

[0098] Standard curve: Prepare a series of nickel standard solutions, cobalt standard solutions, and manganese standard solutions with different concentrations, use an inductively coupled plasma mass spectrometry (ICP-MS) instrument to measure the mass numbers of the standard solutions, and draw the standard curve of nickel, the standard curve of cobalt, and the standard curve of manganese.

[0099] Sample testing: Import the prepared sample solution into the ICP-MS instrument to measure the content of nickel, the content of cobalt, and the content of manganese. According to the standard curve, obtain the mass concentration of nickel, the mass concentration of cobalt, and the mass concentration of manganese, convert to obtain the mass of nickel, the mass of cobalt, and the mass of manganese, and then obtain the number of moles n1 of nickel, the number of moles n2 of cobalt, and the number of moles n3 of manganese. Take n1 + n2 + n3 as the total number of moles of metal elements other than lithium elements, and the molar percentage content of nickel element = n1 / (n1 + n2 + n3) × 100%.

[0100] Content of residual lithium compounds:

[0101] Place the positive electrode sample in an environment with a humidity of 80% and a temperature of 60 °C for storage for 120 h. Then take out the positive electrode sample stored in the above environment, place it in deionized water to dissolve the residual lithium compounds, and then use a potentiometric titrator to titrate and test the dissolved residual lithium compounds to obtain the content of the residual lithium compounds.

[0102] Gram capacity C:

[0103] Cut the positive electrode sheet sample into a circle with a diameter of 14 mm, and weigh the weight of the circular positive electrode sheet sample using an electronic balance. Immerse the separator with a diameter of 16 mm in the electrolyte, and then stack the circular positive electrode sheet sample, the above-mentioned separator, and a lithium sheet with a diameter of 14 mm relative to each other to assemble a button cell.

[0104] The above-mentioned separator, electrolyte are the same as those in Example 1-1, and the thickness of the lithium sheet is 0.4 mm. The battery case of the above button cell is CR1620.

[0105] Charge the above button cell at a constant current density of 0.1C to 4.45V, and then charge it at a constant voltage of 4.45V to 0.01C, which can be regarded as full charge. Then discharge it at a constant current density of 0.1C to 3.0V, which can be regarded as full discharge.

[0106] Record the charge-discharge curve and discharge capacity of the secondary battery.

[0107] Disassemble the button cell, take out the circular positive electrode sheet sample, wash it with dimethyl carbonate (DMC), dry it at 80°C for 12 h, then scrape off the positive electrode material layer on one surface of the positive electrode current collector to obtain a powder material. Calcinate the powder material in an air atmosphere at 400°C for 2 h, and weigh the mass of the calcined powder material on a balance, which is the mass of the positive electrode active material.

[0108] Calculate the gram capacity C: Gram capacity C (mAh / g) = discharge capacity / mass of the positive electrode active material.

[0109] In this application, the gram capacity C of the positive electrode sheet is used to characterize the capacity performance of the positive electrode active material. The higher the C value, the higher the gram capacity performance of the positive electrode active material.

[0110] Volume energy density:

[0111] (1) Test of discharge capacity: At an ambient temperature of 25°C, charge the lithium-ion battery at a constant current of 1C to a voltage of 4.5V, then charge it at a constant voltage of 4.5V to a cut-off current of 0.05C, let it stand for 5 min, and then discharge it at a constant current of 0.2C to a voltage of 3.0V, let it stand for 5 min, and record the discharge capacity at this time as C, with the unit of Wh.

[0112] (2) Dimension test of lithium-ion battery: As Figure 1, along the extending direction of the positive tab 70, i.e., the direction of the arrow in the figure, the lithium-ion battery 02 includes opposite fifth edge 401 and sixth edge 601. The edge where the positive tab 70 is set is the fifth edge 401. The area within 3 mm extending from the fifth edge 401 in the opposite direction of the extending direction of the positive tab 70 is the head region 40. The area within 3 mm extending from the sixth edge 601 along the extending direction of the positive tab 70 is the tail region 60. The remaining area between the head region 40 and the tail region 60 is the middle region 50. The distance between the fifth edge 401 and the sixth edge 601 is the length L of the lithium-ion battery 02. The length of the fifth edge 401 is the width M of the lithium-ion battery 02. The dimension of the lithium-ion battery 02 in the stacking direction is its thickness D. The length L and width M of the lithium-ion battery are measured by scanning with a laser measuring instrument respectively. The thickness Da of the head region 40, the thickness Db of the middle region 50, and the thickness Dc of the tail region 60 are measured with a micrometer respectively; the thickness of each region is measured 3 times, and the average value of the 3 measurements is taken as the thickness of the corresponding region. The thickness D of the lithium-ion battery is calculated by the following formula: D = 1 / 3×(Da + Db + Dc). Among them, the units of D, L, and M are in dm.

[0113] (3) Calculation of the energy density X of the lithium-ion battery: X = C / (D×L×M), and the unit is Wh / L.

[0114] 3C charge lithium plating test:

[0115] Charge at a constant current density of 0.1C until 4.45V, and then charge at a constant voltage of 4.45V until 0.01C, which can be regarded as full charge. Then discharge at a constant current of 0.1C until 3.0V, and record the capacity Q1. Take charging at a constant current of 3C until 4.45V and then discharging at a constant current of 0.1C until 3V as one cycle, and cycle 10 times. Record the last discharge capacity Q2. Then the capacity loss ratio x of these 10 cycles = (Q1 - Q2) / Q1, and x can characterize the severity of lithium plating. If x ≤ 2%, it is determined as no lithium plating. If 2% < x ≤ 5%, it is determined as slight lithium plating. If 5% < x ≤ 8%, it is determined as moderate lithium plating. If x > 8%, it is determined as severe lithium plating.

[0116] Cycle capacity retention rate:

[0117] At 25°C, the lithium-ion battery module is charged at a constant current of 1.0C until the voltage reaches 4.45V, then charged at a constant voltage of 4.45V until 0.05C, and left standing for 10 min; then discharged at a constant current of 0.5C until the voltage reaches 3V, and left standing for 5 min. The above is one cycle. According to the above cycle to 600 cycles, record the discharge capacity of the first cycle as the initial capacity Q0, and the discharge capacity of the lithium-ion battery in the 600th cycle as Qn. Calculate the cycle capacity retention rate of the lithium-ion battery in the 600th cycle through the following formula: Cycle capacity retention rate (%) = Qn / Q0×100%.

[0118] Example 1-1

[0119] <Preparation of the positive electrode plate>

[0120] Hydrophobic composite coating slurry: The polymer material polyvinylidene fluoride and the inert substance particle boehmite are mixed evenly in an N-methylpyrrolidone solvent according to a mass ratio of m = 8:2 to obtain a hydrophobic composite coating slurry with a solid content of 10 wt%.

[0121] Mix the positive electrode active material nickel cobalt manganese ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), the conductive agent Super P, and the binder polyvinylidene fluoride are mixed according to a mass ratio of 97.9:0.9:1.2, add N-methylpyrrolidone (NMP) as a solvent, and formulate it into a slurry with a solid content of 75 wt%. After vacuum stirring evenly, the positive electrode slurry is obtained. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10 μm and dried at 120°C to obtain a positive electrode plate with a single-sided coated positive electrode material layer. The coating weight of the positive electrode material layer is 267.8 mg / 1540 mm 2 . The hydrophobic composite coating slurry is coated on the surface of the positive electrode material layer by a doctor blade method and dried to obtain a positive electrode plate with a single-sided coated positive electrode material layer and a hydrophobic composite coating. The thickness of the hydrophobic composite coating is 0.7 μm. Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode plate with double-sided coated positive electrode material layers and hydrophobic composite coatings, dried at 120°C, and cold-pressed to obtain the positive electrode plate. After cutting and welding the tabs, a positive electrode plate with a specification of 74 mm × 867 mm is obtained for use. Among them, the thickness of the single-sided positive electrode material layer is 42 μm. The specific parameters are shown in Tables 1 to 3.

[0122] <Preparation of the negative electrode plate>

[0123] Mix artificial graphite as the negative electrode active material, styrene-butadiene rubber as the binder, and acetylene black as the conductive agent in a mass ratio of 97.4:1.4:1.2. Add deionized water as the solvent to formulate a slurry with a solid content of 45 wt%. After mixing evenly with a vacuum mixer, the negative electrode slurry is obtained. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6 μm and dried at 120 °C to obtain a negative electrode sheet with a single-sided coated negative electrode material layer. The coating weight of the negative electrode material layer is 142 mg / 1540 mm 2 。Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided coated negative electrode material layer. After drying at 120 °C, it is cold-pressed, and then cut into pieces and welded with electrode tabs to obtain a negative electrode sheet with a specification of 78 mm × 875 mm for standby. Among them, the thickness of the single-sided negative electrode material layer is 54.5 μm.

[0124] <Preparation of electrolyte>

[0125] In an environment with a water content of less than 10 ppm, mix dimethyl carbonate, diethyl carbonate, and ethylene carbonate in a mass ratio of 1:1:1 to obtain an organic solvent. Then add the electrolyte salt LiPF6 to the organic solvent and mix evenly to obtain the electrolyte. Among them, based on the mass of the electrolyte, the mass percentage content of the electrolyte salt is 12.5%, and the rest is the organic solvent.

[0126] <Separator>

[0127] Use a porous polyethylene film with a thickness of 7 μm (provided by Celgard) as the separator.

[0128] <Preparation of lithium-ion battery>

[0129] Stack the positive electrode sheet, separator, and negative electrode sheet prepared above in sequence, with the separator in the middle of the positive electrode sheet and the negative electrode sheet to play an isolation role, and wind to obtain an electrode assembly. Put the electrode assembly into an aluminum-plastic film packaging bag, remove moisture at 80 °C, inject the electrolyte prepared above, and obtain a lithium-ion battery through processes such as vacuum packaging, standing, formation, degassing, and trimming. Among them, the upper limit voltage of formation is 4.15 V, the formation temperature is 70 °C, and the formation standing time is 2 h.

[0130] Examples 1-2 to Examples 1-17

[0131] Except for adjusting the relevant preparation parameters according to Table 1, the rest are the same as Example 1-1.

[0132] Examples 1-18 to Examples 1-32

[0133] Except for adjusting the relevant preparation parameters according to Table 2, the rest are the same as Example 1-1.

[0134] Examples 1-33 to 1-37

[0135] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-1.

[0136] Comparative Example 1

[0137] Except for preparing the positive electrode sheet according to the following method, the rest is the same as Example 1-1.

[0138] Mix the positive electrode active material nickel-cobalt-manganese ternary material NCM811, the conductive agent Super P, and the binder polyvinylidene fluoride in a mass ratio of 97.9:0.9:1.2, add N-methylpyrrolidone (NMP) as a solvent, and formulate it into a slurry with a solid content of 75 wt%. After vacuum stirring evenly, a positive electrode slurry is obtained. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10 μm and dried at 120 °C to obtain a positive electrode sheet with a single-sided coated positive electrode material layer. The coating weight of the positive electrode material layer is 267.8 mg / 1540 mm 2 . Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coated positive electrode material layer, dry it at 120 °C, and cold press it to obtain a positive electrode sheet. Then, after cutting and welding the tab, a positive electrode sheet with a specification of 74 mm × 867 mm is obtained for use. Among them, the thickness of the single-sided positive electrode material layer is 42 μm. The specific parameters are shown in Table 1.

[0139] Comparative Example 2

[0140] Except for preparing the hydrophobic composite coating slurry according to the following method, the rest is the same as Example 1-1.

[0141] Hydrophobic composite coating slurry: Mix the polymer material polyvinylidene fluoride evenly in N-methylpyrrolidone solvent to obtain a hydrophobic composite coating slurry with a solid content of 0%.

[0142] Comparative Examples 3 to 4

[0143] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0144] Table 1

[0145]

[0146]

[0147] Note: " / " in Table 1 represents the absence of relevant parameters.

[0148] It can be seen from Examples 1-1 to 1-37 and Comparative Examples 1 to 4 that in the examples, the contact angle θ of the hydrophobic composite coating satisfies 90° ≤ θ ≤ 150°; the value of the impedance R of the positive electrode sheet satisfies 0.05 ≤ R ≤ 2. The positive electrode sheet has a low content of residual lithium compounds, a relatively high specific capacity, and the obtained lithium-ion battery has a high energy density and a high cycle capacity retention rate, and there is no serious lithium plating. In Comparative Example 1, no hydrophobic composite coating was provided, the adhesion between the positive electrode sheet and the separator was poor, the contact angle between them was small, the impedance of the positive electrode sheet was large, the content of residual lithium compounds was high, and the specific capacity was low. The obtained lithium-ion battery had a low energy density, a low cycle capacity retention rate, and serious lithium plating occurred. In Comparative Example 2, although the contact angle of the hydrophobic composite coating was large, the adhesion between the positive electrode sheet and the separator was good, and the content of residual lithium compounds in the positive electrode sheet was small, but the impedance of the positive electrode sheet was large. The obtained lithium-ion battery had a low energy density, a low cycle capacity retention rate, and serious lithium plating occurred. In Comparative Example 3, the thickness of the hydrophobic composite coating was too small, the hydrophobic effect of the hydrophobic composite coating was poor, the adhesion between the positive electrode sheet and the separator was poor, the contact angle between them was small, and the impedance of the positive electrode sheet was large, the content of residual lithium compounds was high, and the specific capacity was low. The obtained lithium-ion battery had a low energy density, a low cycle capacity retention rate, and serious lithium plating occurred. In Comparative Example 4, the thickness of the hydrophobic composite coating was too high. Although the adhesion between the positive electrode sheet and the separator was good, the contact angle between them was large, and the content of residual lithium compounds in the positive electrode sheet was small, but the impedance of the positive electrode sheet was large. The obtained lithium-ion battery had a low energy density, a low cycle capacity retention rate, and serious lithium plating occurred. Thus, it shows that the lithium-ion battery that meets the present application has good cycle performance and kinetic performance, and takes into account the energy density. Specifically, Figure 2 and Figure 3 are scanning electron microscope pictures of one surface of the positive electrode sheet in Example 1-1 at different magnifications. Figure 2 The small dark regions dispersed like islands in it are the set hydrophobic composite coating 011, and the rest of the region is the positive electrode material layer 012; Figure 3 The regions dispersed and distributed like islands in it are the set hydrophobic composite coating 011, and the rest of the region is the positive electrode material layer 012.

[0149] The thickness d of the hydrophobic composite coating usually affects the kinetic performance, cycle performance and energy density of the lithium-ion battery. It can be seen from Examples 1-1 to 1-8 that when d is within the scope of the present application, the contact angle θ of the hydrophobic composite coating is small, the impedance R of the positive electrode sheet is small, the content of residual lithium compounds is low, and the specific capacity is high. And the obtained lithium-ion battery has a high energy density and a high cycle capacity retention rate, and there is no serious lithium plating. Thus, it shows that when d is within the scope of the present application, the obtained lithium-ion battery has good cycle performance and kinetic performance, and takes into account the energy density.

[0150] The area ratio S1 / S×100% of the hydrophobic composite coating usually affects the kinetic performance, cycling performance and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-9 to 1-16 that when S1 / S×100% is within the scope of this application, the contact angle θ of the hydrophobic composite coating is smaller, the impedance R of the positive electrode sheet is smaller, the content of residual lithium compounds is lower and the specific capacity is higher, and the obtained lithium-ion battery has a higher energy density and a higher cycling capacity retention rate, and there is no serious lithium plating. This shows that when S1 / S×100% is within the scope of this application, the obtained lithium-ion battery has good cycling performance and kinetic performance, and takes into account the energy density. Specifically, as Figure 4 shown, it is a scanning electron microscope photograph of the positive electrode sheet in Example 1-1 along its thickness direction. The lower region of the picture is the positive electrode material layer 012, and the hydrophobic composite coating 011 is distributed above the picture.

[0151] Table 2

[0152]

[0153]

[0154] The average particle size D1 of the inert material particles usually affects the kinetic performance, cycling performance and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-17 to 1-20 that when D1 is within the scope of this application, the contact angle θ of the hydrophobic composite coating is smaller, the impedance R of the positive electrode sheet is smaller, the content of residual lithium compounds is lower and the specific capacity is higher, and the obtained lithium-ion battery has a higher energy density and a higher cycling capacity retention rate, and there is no serious lithium plating. Among them, when S1 / S×100% remains unchanged, the change of D1 has little effect on the adhesion force; but the change of D1 will affect the roughness of the surface of the hydrophobic composite coating, and then its surface tension will also change greatly, so the change trend of the contact angle is more obvious. This shows that when D1 is within the scope of this application, the obtained lithium-ion battery has good cycling performance and kinetic performance, and takes into account the energy density.

[0155] The weight-average molecular weight W of the polymer material usually affects the kinetic performance, cycling performance and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-21 to 1-22 that when W is within the scope of this application, the contact angle θ of the hydrophobic composite coating is smaller, the impedance R of the positive electrode sheet is smaller, the content of residual lithium compounds is lower and the specific capacity is higher, and the obtained lithium-ion battery has a higher energy density and a higher cycling capacity retention rate, and there is no serious lithium plating. This shows that when W is within the scope of this application, the obtained lithium-ion battery has good cycling performance and kinetic performance, and takes into account the energy density.

[0156] The mass percentage content m1 of the inert material particles and the mass percentage content m2 of the hydrophobic polymer material usually affect the kinetic performance, cycle performance, and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-23 to 1-26 that when m1 and m2 are within the scope of this application, the contact angle θ of the hydrophobic composite coating is smaller, the impedance R of the positive electrode sheet is smaller, the content of residual lithium compounds is lower, and the specific capacity is higher. Moreover, the obtained lithium-ion battery has a higher energy density and a higher cycle capacity retention rate, and there is no serious lithium plating. Among them, when the coating amount is certain, if the mass percentage content of the inert material particles is relatively high, such as in Example 26, although the adhesion is still high, the surface tension of the hydrophobic composite coating will change significantly, thereby making its contact angle smaller. This shows that when m1 and m2 are within the scope of this application, the obtained lithium-ion battery has good cycle performance and kinetic performance, and takes into account the energy density.

[0157] The type of the hydrophobic polymer material usually affects the kinetic performance, cycle performance, and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-27 to 1-29 that when the type of the hydrophobic polymer material is within the scope of this application, the contact angle θ of the hydrophobic composite coating is smaller, the impedance R of the positive electrode sheet is smaller, the content of residual lithium compounds is lower, and the specific capacity is higher. Moreover, the obtained lithium-ion battery has a higher energy density and a higher cycle capacity retention rate, and there is no serious lithium plating. When the type of the polymer material is not within the scope of this application, for example, styrene-butadiene rubber is used as the hydrophobic polymer material in Example 1-29. Under the same solid content as in Example 1-1, the coating amount of the hydrophobic polymer coating using styrene-butadiene rubber is only 20%, which makes the contact angle of the hydrophobic composite coating smaller, the impedance of the positive electrode sheet increase, and there are more residual lithium compounds, thereby affecting the cycle capacity retention rate, energy density, and lithium plating situation of the lithium-ion battery. This shows that when the type of the hydrophobic polymer material is within the scope of this application, the obtained lithium-ion battery has good cycle performance and kinetic performance, and takes into account the energy density.

[0158] The types of inert material particles usually affect the kinetic performance, cycling performance, and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-30 to 1-32 that when the types of inert material particles are within the scope of this application, the contact angle θ of the hydrophobic composite coating is small, the impedance R of the positive electrode sheet is small, the content of residual lithium compounds is low, and the specific capacity is high. Moreover, the obtained lithium-ion battery has a high energy density and a high cycling capacity retention rate, and there is no serious lithium plating. When the types of inert material particles are not within the scope of this application, for example, halloysite is used as the inert material particle in Example 1-32. Due to the high water content of halloysite itself, it will affect the overall hydrophobic effect of the positive electrode sheet. Compared with the positive electrode sheets of the above other examples, the content of residual lithium compounds is higher, the contact angle of the hydrophobic composite coating is larger, and the impedance of the positive electrode sheet increases, thereby affecting the cycling capacity retention rate, energy density, and lithium plating situation of the lithium-ion battery. Therefore, it shows that when the types of inert material particles are within the scope of this application, the obtained lithium-ion battery has good cycling performance and kinetic performance, and takes into account the energy density.

[0159] Table 3

[0160]

[0161] The types of positive active materials usually affect the kinetic performance, cycling performance, and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-33 to 1-35 that when the types of positive active materials are within the scope of this application, the contact angle θ of the hydrophobic composite coating is small, the impedance R of the positive electrode sheet is small, the content of residual lithium compounds is low, and the specific capacity is high. Moreover, the obtained lithium-ion battery has a high energy density and a high cycling capacity retention rate, and there is no serious lithium plating. Therefore, it shows that when the types of positive active materials are within the scope of this application, the obtained lithium-ion battery has good cycling performance and kinetic performance, and takes into account the energy density.

[0162] The average particle size D2 of the positive active material usually affects the kinetic performance, cycling performance, and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-36 to 1-37 that when D2 is within the scope of this application, the contact angle θ of the hydrophobic composite coating is small, the impedance R of the positive electrode sheet is small, the content of residual lithium compounds is low, and the specific capacity is high. Moreover, the obtained lithium-ion battery has a high energy density and a high cycling capacity retention rate, and there is no serious lithium plating. Therefore, it shows that when D2 is within the scope of this application, the obtained lithium-ion battery has good cycling performance and kinetic performance, and takes into account the energy density.

[0163] It should be noted that in this text, the term "including", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, such that a process, method or article including a series of elements not only includes those elements, but also includes other elements not expressly listed, or further includes elements inherent to such process, method or article.

[0164] Each embodiment in this specification is described in a related manner. For the same or similar parts among the embodiments, reference can be made to each other, and the differences between each embodiment and other embodiments are emphasized.

[0165] The above are only the preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present application shall be included within the scope of protection of the present application.

Claims

1. A secondary battery, comprising a positive electrode plate, the positive electrode plate comprising a positive electrode material layer, a hydrophobic composite coating and a positive electrode current collector, the positive electrode material layer is located between the hydrophobic composite coating and the positive electrode current collector, the hydrophobic composite coating comprises a hydrophobic polymer material and inert material particles, and the contact angle of the hydrophobic composite coating is θ, 90°≤θ≤150°; The impedance of the positive electrode plate is RΩ, 0.05≤R≤2.

2. The secondary battery according to claim 1, wherein 100°≤θ≤130°; and / or, 0.1≤R≤1.

3. The secondary battery according to claim 1, wherein Based on the area S of the positive electrode material layer, the area of ​​the hydrophobic composite coating is S1, 20%≤S1 / S×100%≤60%.

4. The secondary battery according to claim 3, wherein 30%≤S1 / S×100%≤50%.

5. The secondary battery according to claim 1, wherein The bonding force between the positive electrode plate and the separator is FN / m, 10≤F≤40.

6. The secondary battery according to claim 1, wherein The thickness of the hydrophobic composite coating is d μm, 0.2≤d≤1.

2.

7. The secondary battery according to claim 6, wherein 0.3≤d≤0.7。 8. The secondary battery according to any one of claims 1 to 7, wherein Based on the mass of the hydrophobic composite coating, the mass percentage content m1 of the inert material particles is 10% to 30%, and the mass percentage content m2 of the hydrophobic polymer material is 70% to 90%; The inert material particles include at least one of boehmite, diaspore or quartz sand; The hydrophobic polymer material includes at least one of polyvinylidene fluoride, polysiloxane, polyurethane or polymethacrylate.

9. The secondary battery according to claim 8, wherein The average particle size of the inert material particles is D1 nm, 100≤D1≤500.

10. The secondary battery according to claim 8, wherein The weight average molecular weight of the hydrophobic polymer material is W g / mol, 100000≤W≤500000.

11. The secondary battery according to claim 1, wherein The positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes a nickel element. Based on the total molar amount of metal elements other than lithium elements, the molar percentage of the nickel element is M, and 50%≤M≤95%.

12. The secondary battery according to claim 11, wherein The positive electrode active material comprises lithium nickel cobalt manganese oxide; and / or the average particle size of the positive electrode active material is D2 μm, 5≤D2≤15. 13 . An electronic device comprising the secondary battery according to claim 1 .